Non-linear analysis of plane steel prestressed truss in fire - Fedczuk, Pawel; Skowroński, Wojciech (Journal of Civil Engineering and Management, 2002)
The concept of analysis of 2-D static loaded prestressed steel trusses till failure during fire using a modified method of forces is presented. Failure of steel trusses in fire is based on the criterion of stresses. Behaviour of steel is described by non-linear constitutive model (based on hypo-elastic Ramberg-Osgood formula and Dorn creep theory) and Plem proposition (for string). Both models are approximated in calculations by hyperbolic Norton-Bailey rule. Fire simulates thermal force as an action of high temperature that increases linearly up to some level. The complete formulation of this method is illustrated by the algorithm of model parameters identification. Analysis of results for specific prestressed truss made of ASTM A36 and A421 steel in fire is presented. Frist Published Online: 30 Jul 2012